Collectivism reduces objective mobility trends to public areas during the COVID-19 pandemic - Dang, Junhua; Xiao, Shanshan (Frontiers in Public Health, 2022)
In order to slow down the spread of the coronavirus, staying at home and avoiding going outside have been either strongly recommended or stringently enforced by governments all over the globe. Previous studies found that people with more collectivist orientation were more willing to comply with governmental guidelines and engage in preventive behaviors such as social distancing. However, these studies were based on self-report data within a short period. The current study aims to overcome these limitations by using objective mobility data generated by Google users all over the world during the past two years, thus providing a stronger test for the predictive effect of collectivism on preventive measures in response to the pandemic. We found consistent results at both the US state level (n = 50) and the country/territory level (n = 133), such that people in more collectivistic regions reduced their visits to and length of stay at certain public areas such as parks during the past two years. Our findings emphasize the importance of cultural values in face of global crises.